Analisis Kemampuan Literasi Numerasi dalam Memecahkan Masalah Matematika Bentuk Soal Cerita Kelas IV SD Negeri 1 Sijeruk - Siti Nur Aisyah; Purnamasari, Iin; Nuvitalia, Duwi (CV. Supernova Office Stationary and Printing, 2024)
Numeracy literacy is the knowledge and skill of using various numbers and symbols related to mathematics to solve problems in various contexts in everyday life. Using mathematics skills in various subjects and curricula will broaden and deepen understanding of numeracy. This research discusses the numeracy literacy abilities of Class IV students at SD Negeri 1 Sijeruk. The aim is to analyze students' numeracy literacy skills in solving mathematical problems in the form of story problems. This research uses a qualitative descriptive approach by taking data and information that is in accordance with the facts in the field. The data obtained was analyzed and presented in descriptive form. This research shows that the numeracy literacy skills of class IV students at SD Negeri 1 Sijeruk are quite good, although there are still students who have difficulty understanding and calculating questions.